Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Prepping for the GMAT, I came across the following question:

What is the product of all solutions of:

$$x^2 - 4x + 6 = 3 - |x - 1|?$$

First, I set up two equations, ie:

$$x^2 - 4x + 6 = 3 - (x - 1),$$ and $$x^2 - 4x + 6 = 3 - (-1) \times (x - 1).$$

These factor down to $3$ solutions: $1$, $2$ and $4$. And $8$ is correct solution in the back of the prep book.

However, when plugging $4$ back into the original equation, it reduces to $6 = 3$, so $4$ does not seem to be a solution. Also, when graphing both, they only intersect at $1$ and $2$.

What part of my process (and seemingly the practice books process) is wrong?

share|cite|improve this question
up vote 4 down vote accepted

The solutions to $$x^2-4x+6 = 3-(x-1)$$ are only valid when $x-1 \ge 0$, i.e. when $x \ge 1$. Likewise, the solutions to $$x^2-4x+6 = 3+(x-1)$$ are only valid when $x-1 \le 0$, i.e. when $x \le 1$.

Solving the first equation gives $x=1,2$, both of which are valid. Solving the second gives $x=1,4$. Notice that in this latter case $4$ is not valid since $4 \nleq 1$, and so the only solutions to $x^2-4x+6=3-\left|x-1\right|$ are $x=1,2$. (The textbook is wrong!)

share|cite|improve this answer
Thanks Clive. Makes sense. Plotting the equation shows that as well:… – jim_shook Aug 2 '12 at 1:38

You seem to be right: only intersections at 1 and 2. For 4 you get 16=0.

share|cite|improve this answer

Hint $\rm\,\ |x\!-\!1| = (x\!-\!1)(3\!-\!x).\:$ Thus either $\rm\: x=1\:$ or $\rm\: 3\!-\!x = |x\!-\!1|/(x\!-\!1) = sgn(x\!-\!1).\:$ Therefore $\rm\:x = 3-sgn(x\!-\!1)\:\Rightarrow\:x>1\:\Rightarrow\: x = 3\!-\!1 = 2. $

share|cite|improve this answer
May I suggest saying something to the effect of "The given equation is equivalent to $|x-1|=(x-1)(3-x)$" instead, so it doesn't look like you're stating an identity? I was confused for a moment. – Rahul Aug 2 '12 at 6:15

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.